Oliver and Albert, Friends Forever - Van Leeuwen, Jean; Schweninger, Ann (New York : Phyllis Fogelman Books, 2000)
Oliver makes friends with Albert, the new boy in class, and they have fun together, playing kickball and collecting bugs.
Keywords: Pigs -- Fiction; Friendship -- Fiction; Schools -- Fiction